2010
DOI: 10.1111/j.1745-4549.2009.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Piper Extracts on Pork Stability

Abstract: Antioxidant effects of black pepper (Piper guineense) essential oil and oleoresin on fresh and cooked ground pork patties were evaluated at inclusion levels of 0.25 and 0.50% of meat weight. Patties were stored for 16 weeks at room temperature (27 ± 1C). Thiobarbituric acid (TBA) and peroxide values (PVs) of patties were measured as indicators of lipid oxidation at 27 ± 1C for 16 weeks. Mean TBA and PVs were high for the controls (no Piper extracts), 16.78 mg malonaldehyde/Kg and 28.52 MEK/g, and 11.76 mg malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Rojas and Brewer, 128 Nissen et al, 130 Lara et al, 131 Sebranek et al, 133 Doolaege et al, 136 Sasse et al, 102 Lara et al, 131 Ugwuona, 177 McCarthy et al 148 …”
Section: Pork Productsmentioning
confidence: 97%
See 1 more Smart Citation
“…Rojas and Brewer, 128 Nissen et al, 130 Lara et al, 131 Sebranek et al, 133 Doolaege et al, 136 Sasse et al, 102 Lara et al, 131 Ugwuona, 177 McCarthy et al 148 …”
Section: Pork Productsmentioning
confidence: 97%
“…Peppers are also used as antioxidant agents in meat products. One study compared the antioxidant power of black pepper ( Piper guineense ) essential oil with rosemary oleoresin in raw and cooked ground pork, and found that black pepper oil was effective at reducing TBARS . The addition of different species of the genus Capsicum also conferred an antioxidant effect in raw and cooked pork …”
Section: Natural Antioxidantsmentioning
confidence: 99%